Mental Status Changes in Severe Babesiosis - Matthew J. Navarro; Frederic Karim; Rakan Al-Ghanamah; Steven B. Maron (Annals of Internal Medicine: Clinical Cases)
Babesiosis is a tick-borne disease caused by an intraerythrocyte protozoon. We present a unique case of a patient who was infected with babesiosis and subsequently developed severely altered mental status, which dramatically improved after erythrocyte exchange transfusion. This case illustrates that mental status changes can be a diagnostic marker of severe babesiosis and may indicate the need for erythrocyte exchange transfusion.